Hairpin loop-enhanced fluorescent copper nanoclusters and application in S1 nuclease detection. Issue 2 (11th December 2017) - Peng, Xian-sui; Chen, Si-Yu; Ou, Li-Juan; Luo, Feng-Wu; Qin, Si-Wen; Sun, Ai-ming
Abstract : A novel hairpin DNA template with an AT24 double strand stem and a six-base loop was demonstrated for the first time to prepare CuNCs with dramatically enhanced fluorescence and applied for the sensitive detection of S1 nuclease. Abstract : Novel highly fluorescent copper nanoclusters (CuNCs) were prepared by using 24 adenine–thymine pair dsDNA (AT24) with six-base (X6) loops (AT24-X6-hairpin DNA) as an effective template. The AT24 double strand stem serves as a template for CuNC formation, and the six-base sequence loop acts as specific regions to enhance the fluorescence intensity of CuNCs. Relative to the AT24-CuNCs, AT24-X6-hairpin CuNCs have greater fluorescence (5 times enhancement). What's more, the influence of the hairpin loop with different base types and base numbers on the fluorescence of CuNCs was first proposed and investigated. By choosing an AT24 double strand stem, any types of base loops can enhance the fluorescence of CuNCs. However, the fluorescence enhancement would be reduced with an increasing number of hairpin loop sequences. Besides this, the successful detection of S1 nuclease demonstrates its potential to be a new and robust fluorescent probe for sensing applications.